Educational activities in the Program for Education through Work for Health - Rafaela Braga Pereira Velôso; Josicélia Dumêt Fernandes; Rosana Maria de Oliveira Silva; Ana Lúcia Arcanjo Oliveira Cordeiro; Gilberto Tadeu Reis da Silva; Elaine Andrade Leal Silva (Escola Anna Nery)
Abstract Objective: To describe the educational activities of the Program for Education through Work for Health (PET-Health) developed in family health units of a municipality in the Northeast of Brazil. Method: Qualitative study with 16 preceptors interviewed in the months of March and April 2016. Inclusion criterion was adopted: preceptors who worked in family health units linked to the program, for at least two years. Were excluded workers on vacations, maternity leave or on leave for various reasons. The data were interpreted according with Bardin's content analysis method. Results: It was evidenced that the PET-Health involves users in health education actions in the formation of educational groups, recreational activities and income generation workshops, and permanent education activities for health service workers through training, collective actions and induction of changes in daily work. Conclusion and implications for practice: Educational activities of the PET-Health, according to the reality and needs of health services, is a differential that qualifies the training process of students and workers, while promoting education for the health of users through integrated and intersectoral actions.